Films on Ice Cinemas of the Arctic. - MacKenzie, Scott (Traditions in World Cinema Ser., 2014)
The first book to address the vast diversity of Northern circumpolar cinemas from a transnational perspective, Films on Ice: Cinemas of the Arctic presents the region as one of great and previously overlooked cinematic diversity.